Massive Fire Incidents of Multiple Aboveground Storage Tanks due to Vapor Cloud Explosion - Shoichi Yoshida (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
The vapor cloud explosion (VCE) begins with a release of a large quantity of flammable vaporing liquid from a storage tank, transportation vessel or pipeline. If VCE occurs in an oil storage facility, multiple tanks burn simultaneously. There is no effective firefighting method for multiple tanks fire. It will be extinguished when oil burned out spending several days. Many incidents of multiple tanks fire due to VCE have occurred all over the world in recent 50 years. This paper reviews the past 6 incidents of multiple tanks fire due to VCE.